PENGARUH PENERAPAN SISTEM E-FILING TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL PEMODERASI - Muhamad Andrian Afifi; Evi Maria (Sekolah Tinggi Teknologi Kedirgantaraan, 2021)
This study aims to determine the effect of the application of the e-filing system on taxpayer compliance with internet understanding as a moderating variable in West Mataram KPP Pratama. The research data were obtained from questionnaires (primary) which were distributed to taxpayers registered at KPP Pratama Mataram Barat using accidental sampling method. The population in this study were individual taxpayers who were registered at KPP Pratama West Mataram. The sample used in this study were 100 respondents. The questionnaire was tested for validity and reliability before the study. The classical assumption test used was the multicollinearity test, heteroskdacity test, and normality test. Hypothesis test used is multiple linear regression test and MRA test. The results of this study indicate that (1) The application of the E-Filing System has a positive and significant effect on Taxpayer Compliance, so that the hypothesis can be accepted. (2) Understanding of the internet has a positive and significant effect on taxpayer compliance, so that the hypothesis can be accepted. (3) Understanding the Internet has a positive and significant effect on the relationship between the application of the e-filing system to taxpayer compliance, so that the hypothesis can be accepted.